Loss-of-function/gain-of-function polymorphisms of the ATP sensitive P2X7R influence sepsis, septic shock, pneumonia, and survival outcomes - Guggemos, Johanna; Fuller, Stephen J.; Skarratt, Kristen K.; Mayer, Benjamin; Schneider, E. Marion (Frontiers in Immunology, 2024)
Extracellular ATP (eATP) released during trauma opens an ion channel and macropore, P2X7 receptor (P2X7R), resulting in massive calcium influx, potassium efflux and inflammasome activation. P2X7 genotypes influence the eATP induced response and a highly active P2X7R even induces cell death. Single nucleotide polymorphisms (SNPs) of P2X7 gene (P2RX7) influence both function and signaling by eATP, including pathogen control and immunity. We here investigated the distribution of 16 SNPs of P2RX7 characterized as either loss-of-function (LOF) or gain-of-function (GOF) phenotypes in n=105 patients admitted to Intensive Care of Ulm University Hospital with sepsis, septic shock, and pneumonia between June 2018 and August 2019. It was hypothesized that LOF variants might protect against hyperinflammation and excessive systemic inflammation, but would impair the immunity required to control secondary infections such as pneumonia. In contrast, a more active P2X7R could either be essential for immune activation, calcium signaling and phagocytosis, or lead to P2X7-mediated cell death.Mutation of the LOF SNP rs17525809 (T253C) likely attenuating P2RX7 function was found more frequently present in patients with septic shock, and non-septic trauma patients when compared to sepsis. The LOF SNP rs2230911 (C1096G) in strong linkage disequilibrium (LD) with the mRNA stability SNP rs3751142 (G1628T), coordinates the CRAC channel and cholesterol, was found to be